A tradução inglesa de memórias póstumas de Brás Cubas: uma abordagem sistêmico-funcional - Nunes, Camila Matos Venesiano (2021)
In the nineties, the figure of the subservient translator was replaced by that of the visibly active translator, understood as a subject inserted in a cultural, ideological, political and psychological context, factors that cannot be ignored in the translation. The translator is not extinguished when translating a work, as the translator is not free from the sociocultural impositions of the community of which the translator is a part; the difference in the cut-out of the world between cultures; and the linguistic injunctions that limit the lexicogramatical choices available to the translator. Therefore, these choices are not neutral, as explained by the notion of equivalence, defined in terms of contextual meanings, and not formal meanings. There is also the fact that the original language has several X agnates, allowing the translator the option of translating item X or one of its agnates. The objective of this doctoral thesis is to compare two English translation versions of the book The Posthumous Memoirs of Brás Cubas (Memórias Póstumas de Brás Cubas), by Machado de Assis, carried out respectively by Gregory Rabassa (1997) and Flora Thomson-DeVeaux (2020), in order to verify how the choices made by the translators, although in articulation with the original text, show different representations of reality resulting from the context in which they are inserted. The research is supported by Systemic-Functional Linguistics (SFL), a theoretical-methodological proposal, described as a semantic-functional approach to language, which seeks to understand how people use language in different social contexts, to make sense of the world and of each one. For SFL, it is possible to verify structural, lexical, grammatical and semantic traits in texts constituting a given genre, through metafunctions. The research seeks to answer the following questions: (a) how are the ideational, interpersonal and textual meanings articulated in the two translated versions of The Posthumous Memoirs of Brás Cubas into English?; and (b) what are the consequences of these changes for the macrotextual meaning of the versions and characterization of the translators' style? The research shows that the textual meaning has hardly changed in both translations; the terms that express the ideational meaning showed that Rabassa's translation is closer to the original than DeVeaux's, with evident reflections on interpersonal meaning, in the sense that, perhaps, the second resembles more with the linguistic flow of the English language. In general terms, the translation of Rabassa (1997) is closer to the original Memórias Póstumas de Brás Cubas than that of Thompson-DeVeaux (2020)